Enhanced Flexible Mold Lifetime for Roll-to-Roll Scaled-Up Manufacturing of Adhesive Complex Microstructures - Kim, Jae-Kang (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH.